Disulfidptosis ‒ related lncRNAs are biomarkers of prognosis and immune response in Head and Neck Squamous Cell Carcinoma - Ruilin Wang; Qi Zhang; Yuxiu Ma; Xuelin Liu; Tian Lan; Hongling Li (Brazilian Journal of Otorhinolaryngology)
Objective: This study aims to explore the role of Disulfidptosis-Related long Non-Coding RNAs (DRlncRNAs) in the prognosis and immune infiltration of Head and Neck Squamous Cell Carcinoma (HNSCC). Methods: Using bioinformatics approaches, this study investigates the prognostic significance of DRlncRNAs in HNSCC patients and their potential association with the immune microenvironment. RNA sequencing data and clinical information for HNSCC were obtained from The Cancer Genome Atlas (TCGA) database. DRlncRNAs were identified through Pearson correlation analysis, and a prognostic model consisting of six DRlncRNAs was constructed using Least Absolute Shrinkage and Selection Operator (LASSO) regression, along with univariate and multivariate Cox analyses. Results: The predictive performance of the model was assessed using Receiver Operating Characteristic (ROC) curves and Principal Component Analysis (PCA), and further validated using calibration curves, a nomogram, and univariate/multivariate Cox analyses. In addition to functional enrichment analysis, the associations between the model and Tumor Mutation Burden (TMB), immune cell infiltration, and drug sensitivity were also examined. Conclusion: We developed a novel predictive model composed of six DRlncRNAs to predict the prognosis of HNSCC patients and proposed potential clinical therapeutic targets from the perspective of disulfidptosis. Level of evidence: Level 5.